2012
DOI: 10.1080/15205436.2011.568316
|View full text |Cite
|
Sign up to set email alerts
|

Choosing the Right Media for Mobilization: Issue Advocacy Groups' Media Niches in the Competitive Media Environment

Abstract: Issue advocacy groups play a central role in today's political system, and the choices they make concerning media and communication have lately been a scholarly concern. This study investigates how issue advocacy groups choose media and communication technologies from the perspective of uses and gratifications approach and the niche theory. Drawing upon a national telephone survey of 209 randomly chosen advocacy groups in the United States, the findings suggest that new communication technologies (including e-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Reporters, for instance, tend to direct such information to their own or even a group's website. In support of this, a recent study found that even advocacy groups themselves tend to differentiate appropriate media outlets for different strategic efforts, choosing a 'niche' medium for a 'niche' activity (Min and Kim, 2012).…”
Section: Discussionmentioning
confidence: 93%
“…Reporters, for instance, tend to direct such information to their own or even a group's website. In support of this, a recent study found that even advocacy groups themselves tend to differentiate appropriate media outlets for different strategic efforts, choosing a 'niche' medium for a 'niche' activity (Min and Kim, 2012).…”
Section: Discussionmentioning
confidence: 93%
“…At the heart of the replacement hypothesis is the notion that individuals select among media based on how well a particular outlet meets their needs and goals. The ecology-based “theory of the niche” is a useful framework for taking this basic idea and more directly examining the competitive relationship between the Internet and older media (e.g., Kaynay and Yelsma 2000; Min and Kim 2008; Okazaki and Hirose 2009).…”
Section: Theory and Expectationsmentioning
confidence: 99%
“…We contribute to this literature by applying theories from ecology to understand the competitive dynamics between the Internet and traditional media outlets. We draw on niche theory, a framework that previous scholars have used to examine competition between new and older media (e.g., Dimmick et al 2000; Dimmick et al 2004; Min and Kim 2008). Our study is the first to test hypotheses derived from this theory on a large, national sample and to examine the attitudinal consequences of replacement.…”
mentioning
confidence: 99%
“…Kim and colleagues (2010) find that issue advocacy groups facilitate information-rich, grassroots-oriented public mobilization (i.e., informational mobilization and participatory mobilization) more than ever before and that there seems to be a shift in the focus of advocacy groups' strategic activities from traditional, inside lobbying to public mobilization, even among mainstream issue interest groups. Kim and her colleagues (Kim and McCluskey 2009;Kim et al, 2010;Min and Kim 2012) attribute these trends to the adoption of "niche media" (especially digital communication technologies) based on empirical evidence indicating consistent positive associations between the adoption of various digital technologies and groups' public mobilization activities. This is true even after controlling for organizational resources and institutionalization factors (e.g., total revenue, history, location in Washington, D.C., formal membership, dues collection, and political action committees).…”
Section: Why Now? the New Media Environment And The Reconfiguration Of Political Communicationmentioning
confidence: 99%
“…This is true even after controlling for organizational resources and institutionalization factors (e.g., total revenue, history, location in Washington, D.C., formal membership, dues collection, and political action committees). Kim and colleagues (Kim and McCluskey 2009;Kim et al 2010;Min and Kim 2012) explain that the technological attributes of digital media-the lower cost of collective action, increased availability of information, increased identification with issues, and blurred distinction between public and private-may have contributed to groups' public mobilization and organization of collective action. Min and Kim (2012) support this idea by showing that groups clearly understand the utility of niche media in public mobilization.…”
Section: Why Now? the New Media Environment And The Reconfiguration Of Political Communicationmentioning
confidence: 99%